Evaluation of Drug Management in the Planning, Procurement, and Distribution Stages at the Hospital Pharmacy Installation - Sinaga, Clara Ritawany; Tikes, Roivelisko; Simanullang, Raymon (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Pharmacy department is a very important part of the hospital because it is the center of drug management and a source of hospital income. This study aims to determine drug management at the planning, procurement, and distribution stages at the Hospital Pharmacy Installation. This type of research is a descriptive evaluative research with qualitative methods. Data collection was carried out retrospectively on drug management indicators at the planning, procurement, and distribution stages, prospectively by conducting direct interviews and using random sampling methods. Data analysis uses and according to the Indonesian Ministry of Health in 2008, WHO in 1993 and Pudjaningsih in 1996. The validity test used is expert judgment. The results of the study showed that the conformity of drug items with the National Formulary was 18%, the frequency of procurement of each drug item was 5,6x/year, 13% invoice errors, the frequency of delayed payments by the hospital against the specified time was 70%, the level of drug availability was 46 months, the percentage of dead stock was 1%, the compatibility between drugs and stock cards was 100%. This shows that the indicators of drug management at the planning, procurement, and distribution stages are still not efficient, because there are still several indicators that do not comply with the established standards so that improvements need to be made.